Detecting anomalous traffic in the controlled network based on cross entropy and support vector machine. (1st March 2019) - Han, Weijie; Xue, Jingfeng; Yan, Hui
Abstract : Network anomaly detection is an effective way for analysing and detecting malicious attacks. However, the typical anomaly detection techniques cannot perform the desired effect in the controlled network just as in the general network. In the circumstance of the controlled network, the detection performance will be lowered due to its special characteristics including the stronger regularity, higher dimensionality and subtler fluctuation of its traffic. On the motivation, the study proposes a novel classifier framework based on cross entropy and support vector machine (SVM). The technique first subtracts the representative traffic characteristics from the network traffic and defines a 7‐tuple feature vector for the controlled network by extending the traditional 5‐tuple representation of the usual network. Then the probability distributions and cross entropies of the 7 tuples are calculated during the defined statistical window so as to generate the 7‐tuple cross‐entropy feature vector for profiling the network traffic fluctuation in the controlled network. Finally, the multi‐class SVM classifier is trained by importing the 7‐tuple cross‐entropy feature vectors. Experimental results show that the proposed classifier can achieve higher detection rates and is more suitable to be used in the controlled network than the typical detection techniques.